New Application’s Approach to Unified Power Quality Conditioners for Mitigation of Surge Voltages - Yeison Alberto Garcés Gomez; Nicolás Toro García; Fredy E. Hoyos (Journal of Electrical and Computer Engineering)
This paper outlines a new approach for the compensation of power systems presented through the use of a unified power quality conditioner (UPQC) which compensates impulsive and oscillatory electromagnetic transients. The newly proposed control technique involves a dual analysis of the UPQC where the parallel compensator is modelled as a sinusoidal controlled voltage source, while the series compensator is modelled as a sinusoidal controlled current source, opposed to the traditional approach where the parallel and series compensators are modelled as current and voltage nonsinusoidal sources, respectively. Also a new compensation algorithm is proposed through the application of the theory of generalized reactive power; this is then compared with the theory of active and reactive instantaneous power, or pq theory. The results are presented by means of simulations in MATLAB-Simulink®.